Output Filter Design for a Novel Dual-Input PV-Wind Power Converter by Energy Balance Principle - Chih-Lung Shen; You-Sheng Shen (Applied Sciences, 2016)
In this paper, a detailed and systematic derivation of the output filter in a novel dual-input photovoltaic (PV)-wind converter (DIPWC) is presented. The theoretical derivation is based on an energy balance principle. While the DIPWC operates in steady state, the amount of charged energy of the output filter will be equal to that of the energy pumped away within one switching cycle. From this zero net change in energy, the minimum value of the output filter can be found. With the determined value, the DIPWC is able to operate in continuous conduction for high power applications. The developed procedure of the inductance determination can be applied to other types of dual-input converters. Therefore, it makes significant contributions to the design toward a green-energy, multi-input converter. To verify the correctness of the mathematical analysis, the DIPWC—with the derived output inductance—is built and tested. Practical measurements and results have verified the inductance determination.